Understanding Reconstruction Halal Products for Halal Businesses in Tana Toraja - Fasiha, Fasiha; Jabani, Muzayyana; Kamal, Helmi; Abdullah, Muh Ruslan (LP2M IAIN Palopo, 2021)
Abstract[English]:There is an interesting phenomenon in Tana Toraja about the halal product label. Countless businessmen put a halal label on their business without having any legal halal certificate. This article has some objectives. It aims at conveying the understanding level owned by businessmen, elaborating whether the understanding affects the decision on having halal certificate, explaining the understanding construction of halal product of Muslim businessmen and informing the factors that cause malpractice of halal product. The finding result proved that; (1) the lack decision of businessmen to make halal certificate; (2) some stakeholders such as MUI, KEMENAG Tana TorajaÂ and preachers had conducted understanding reconstruction; (3) the result also showed that malpractice of halal product was caused by haram materials that were cheaper than halal ones, halal label was solely marketing strategy and halal certificate spent lots of money.Â Abstrak[Indonesia]:Ada fenomena menarik di Tana Toraja tentang label produk halal. Tak terhitung banyaknya pengusaha yang memasang label halal pada usahanya tanpa memiliki sertifikat halal yang sah. Artikel ini memiliki beberapa tujuan. Hal ini bertujuan untuk menyampaikan tingkat pemahaman yang dimiliki oleh pengusaha, mengelaborasi apakah pemahaman tersebut mempengaruhi keputusan memiliki sertifikat halal, menjelaskan konstruksi pemahaman produk halal pengusaha muslim dan menginformasikan faktor-faktor penyebab malpraktik produk halal. Hasil temuan membuktikan bahwa; (1) kurangnya keputusan pengusaha untuk membuat sertifikat halal; (2) beberapa pemangku kepentingan seperti MUI, KEMENAG Tana Toraja dan para mubaligh telah melakukan rekonstruksi pemahaman; (3) Hasil penelitian juga menunjukkan bahwa malpraktik kehalalan produk disebabkan oleh bahan haram yang lebih murah dari yang halal, label halal semata-mata strategi pemasaran dan sertifikat halal menghabiskan banyak uang.Â